Solid acid catalyst as well as preparation method and application thereof
By using a solid acid catalyst with a specific composition in the reaction of toluene disproportionation and alkyl transfer, the problems of high reaction temperature and hydrogen consumption in the prior art are solved, and a low-temperature and efficient catalytic effect is achieved, and energy consumption and material consumption are reduced.
Patent Information
- Application Number
- CN202311221012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-21
AI Technical Summary
In the prior art, the temperature and hydrogen consumption of toluene disproportionation and alkyl transfer reaction are relatively high, resulting in increased energy consumption and material consumption, making it difficult to achieve energy-saving and efficient production.
A solid acid catalyst is used, which consists of a silicon oxide support, Group IVB and Group IVA metal oxides, Group VIB and Group VIII metal oxides and sulfate ions. Through specific component ratios and preparation methods, the acid properties and reaction activity of the catalyst are regulated to achieve a low-temperature alkyl transfer reaction.
In the reaction of toluene disproportionation and alkyl transfer, the catalyst exhibits the characteristics of low reaction temperature, low hydrogen consumption and high conversion rate, which significantly reduces energy consumption and material consumption and improves production efficiency.
Smart Images

Figure BDA0004460589560000091 
Figure BDA0004460589560000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid catalysts, and specifically relates to a solid acid catalyst and a preparation method and application thereof. Background Art
[0002] Xylene is an important basic organic raw material. The toluene disproportionation and transalkylation unit in the aromatics complex is one of the important ways to produce xylene in industry. With the shortage of energy, achieving energy saving and high efficiency in xylene production is an urgent issue to be solved. Reducing the energy consumption and material consumption in the disproportionation and transalkylation process by improving the catalytic performance of the catalyst is an important way to reduce costs and increase efficiency. The transalkylation reaction is an acid-catalyzed reaction, and regulating the acid properties of solid acids to match the reaction is a research focus of catalyst design. Solid acid catalysts are widely used in various industrial production processes, among which the solid superacid obtained after sulfation treatment is an important type of solid acid. Metal oxides can generally achieve a significant increase in acid strength after sulfation treatment. By adding additives to regulate the distribution of acid strength, the acid properties of the catalyst can be matched with the reaction.
[0003] CN113492016A discloses a two-component catalyst for toluene disproportionation and transalkylation and a preparation method thereof. The catalyst comprises a modified needle-shaped MOR molecular sieve and a modified nano ZSM-5 molecular sieve. The modified needle-shaped MOR molecular sieve is prepared by impregnating and modifying a needle-shaped hydrogen-type MOR molecular sieve with a length-to-diameter ratio of 3 to 10:1 with an inorganic oxide; the modified nano ZSM-5 molecular sieve is prepared by impregnating and modifying a hydrogen-type nano ZSM-5 molecular sieve with a particle size of 50 to 300 nm with an inorganic oxide. The inorganic oxide is one or more of the oxides of Co, Mo, Ru, Cu, Be and W. When the catalyst is used, the reaction temperature is required to be 300 to 500°C and the hydrogen-to-hydrocarbon ratio is 10:1-1:1.
[0004] CN102909066A discloses a toluene disproportionation and transalkylation catalyst. The catalyst is composed of a hydrogen-type EU-1 / Beta composite molecular sieve, an inorganic refractory oxide, and a second metal component. CN102909068A discloses a toluene disproportionation and transalkylation catalyst. The catalyst is composed of a hydrogen-type EU-1 / ZSM-5 composite molecular sieve, an inorganic refractory oxide, and a second metal component.
[0005] In summary, the current research on toluene disproportionation and transalkylation catalysts is mostly based on molecular sieve systems, and the reaction temperature and hydrogen consumption are generally high. Summary of the invention
[0006] In view of the problems of high temperature and hydrogen consumption of transalkylation reaction in the prior art, the present invention provides a new solid acid catalyst and its preparation method and application. The catalyst is used for toluene disproportionation and transalkylation reaction, and has the characteristics of low reaction temperature, low hydrogen consumption and high conversion rate.
[0007] The first aspect of the present invention provides a solid acid catalyst, which comprises, based on the weight of the catalyst and measured by mass fraction:
[0008] a) 50% to 98% of a silicon oxide carrier;
[0009] b) 1% to 30% of at least one metal selected from Group IVB and Group IVA, calculated as the corresponding metal oxide;
[0010] c) 0.01% to 10% of at least one metal selected from Group VIB and Group VIII;
[0011] d) 0.1% to 10% sulfate ion;
[0012] The ratio of the B acid amount to the strong L acid amount of the catalyst is 20:1 to 1:20, preferably 10:1 to 1:10, and more preferably 10:1 to 1:5, for example, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:10, etc., and any value in the range formed by any two of these values.
[0013] According to the present invention, preferably, the catalyst comprises:
[0014] a) 65% to 88% of a silicon oxide carrier;
[0015] b) 10% to 25% of at least one metal selected from Group IVB and Group IVA, calculated as the corresponding metal oxide;
[0016] c) 1% to 5% of at least one metal selected from Group VIB and Group VIII;
[0017] d) 1% to 5% sulfate ions.
[0018] According to the present invention, the silicon oxide of component a) is mesoporous silicon oxide.
[0019] According to the present invention, component b) is at least one selected from Zr, Ti, and Sn, preferably Sn.
[0020] According to the present invention, component c) is at least one selected from Cr, Mo, W, Co, Ni, and Ru, and more preferably at least one selected from W and Ni.
[0021] The second aspect of the present invention provides a method for preparing the solid acid catalyst, comprising:
[0022] (1) mixing a template, a silicon source, a source of component c), and a solvent, and then dropwise adding ammonia water to obtain a mixture;
[0023] (2) aging the mixture obtained in step (1) to obtain a gel, and then subjecting the mixture to a first calcination to obtain a solid;
[0024] (3) mixing the solid obtained in step (2), the source of component b) and the precipitant, and performing a first hydrothermal reaction, a second hydrothermal reaction and a third hydrothermal reaction, and then separating to obtain a solid;
[0025] (4) treating the solid obtained in step (3) with a sulfating agent, and then subjecting the solid to a second calcination to obtain the catalyst.
[0026] In step (3), the reaction temperature of the second hydrothermal reaction is higher than the reaction temperature of the first hydrothermal reaction; the temperature of the third hydrothermal reaction is higher than the reaction temperature of the second hydrothermal reaction. Preferably, the reaction temperature of the second hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the first hydrothermal reaction. The reaction temperature of the third hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the second hydrothermal reaction.
[0027] According to the present invention, in step (1), the template is at least one of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride, preferably P123. The silicon source is tetraethyl orthosilicate. The solvent is ethanol. The source of component c) is a metal salt containing component c), preferably a soluble metal salt. Further, the source of component c) is at least one of nitrate, acetate and chloride containing the metal of component c). The mass concentration of the ammonia water is 25% to 28%.
[0028] According to the present invention, in step (1), the molar ratio of the feed materials is, silicon source is calculated as SiO2: template: solvent: NH3: H2O = 1: 0.001~1: 20~200: 0.001~1: 1~50, preferably, silicon source is calculated as SiO2: template: solvent: NH3: H2O = 1: 0.01~0.1: 50~150: 0.01~0.5: 10~30.
[0029] According to the present invention, further, in step (1), the mixture is stirred thoroughly until it is completely dissolved. The stirring temperature is 20 to 60°C, preferably 30 to 40°C.
[0030] According to the present invention, further, in step (1), the addition time of ammonia water is 0.1 to 0.5 hours. After the ammonia water is added dropwise, it is fully stirred. The stirring temperature is 20 to 60° C., preferably 30 to 40° C., and the stirring time is 10 to 50 hours, preferably 15 to 25 hours.
[0031] According to the present invention, in step (2), the aging temperature is 30-60°C, the aging time is 10-60 hours, preferably 20-50 hours. The relative humidity of aging is 30%-60%. The meaning of relative humidity is the percentage of water vapor pressure in the air to the saturated water vapor pressure at the same temperature.
[0032] According to the present invention, in step (2), the conditions for the first calcination are: a calcination temperature of 200 to 700° C., preferably 300 to 500° C., and a calcination time of 1 to 10 hours, preferably 2 to 5 hours.
[0033] According to the present invention, the source of component b) in step (3) is a metal salt containing component b), preferably a soluble metal salt. Further, the source of component b) is at least one of nitrate, acetate and chloride containing the metal of component b).
[0034] According to the present invention, the precipitant in step (3) is at least one of urea, KOH and NaOH. The molar ratio of the metal in component b) to the precipitant is 1:1 to 1:30, preferably 1:5 to 15.
[0035] According to the present invention, the mixing in step (3) is followed by sufficient stirring at a temperature of 15 to 40° C. and a stirring time of 3 to 12 hours.
[0036] According to the present invention, in step (3), the device for the hydrothermal reaction is a hydrothermal kettle. The temperature of the first hydrothermal reaction is 120-150°C and the time is 2-20h; the temperature of the second hydrothermal reaction is 150-170°C and the time is 2-20h. The temperature of the third hydrothermal reaction is 170-200°C and the time is 2-20h. The reaction times of the first hydrothermal reaction, the second hydrothermal reaction and the third hydrothermal reaction can be the same or different.
[0037] According to the present invention, in step (3), the solid obtained after separation can be washed and / or dried. The washing can be carried out by at least one of ethanol and deionized water. The drying temperature is 60 to 120° C. and the drying time is 2 to 20 hours.
[0038] According to the present invention, in step (4), the sulfating agent is at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate. The sulfating agent exists in the form of a solution. The concentration of the sulfating agent solution is 0.1 to 3 mol / L, preferably 0.5 to 1.5 mol / L. The mass of the solid powder and the volume of the sulfating agent satisfy the following relationship: 1 g / 10 mL to 1 g / 200 mL. The sulfating agent treatment method is immersion, preferably immersion under stirring. The temperature of the sulfating treatment is 15 to 40 ° C, and the time is 2 to 20 hours. Drying can be performed after the sulfating treatment. The drying temperature is 60 to 120 ° C, and the drying time is 2 to 20 hours.
[0039] According to the present invention, in step (4), the atmosphere of the second calcination is an oxygen atmosphere, preferably air. The temperature of the second calcination is 300-650° C., and the time is 2-20 hours.
[0040] The third aspect of the present invention provides the use of the solid acid catalyst or the solid acid catalyst prepared by the above method in toluene disproportionation and transalkylation reactions.
[0041] According to the present invention, the reaction conditions of the application are: reaction temperature is 100-500°C, preferably 100-300°C, more preferably below 300°C, reaction pressure is 1.0-8.0MPa, hydrogen-to-hydrocarbon molar ratio is 0.1-10, preferably 0.1-5, liquid raw material weight space velocity is 0.5-10h -1 .
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] 1. The catalyst of the present invention comprises: a) 50% to 98% of a silicon oxide carrier; b) 1% to 30% of at least one metal selected from the IVB group and the IVA group, calculated as the corresponding metal oxide; c) 0.01% to 10% of at least one metal selected from the VIB group and the VIII group; d) 0.1% to 10% of sulfate ions; the ratio of the amount of B acid to the amount of strong L acid in the catalyst is 20:1 to 1:20. The inventor of the present invention has found through research that in the disproportionation and transalkylation reactions, the ratio of strong L acid to B acid in the catalytic material is related to the transfer process of active protons on the catalyst surface during the reaction, and the addition of bimetallic components can achieve the regulation of the ratio to obtain better catalytic performance. The sulfate ions and metal oxides synthesized in situ dispersed in the pore structure of the mesoporous silica material have higher acid strength and acid density, and can achieve transalkylation reactions at lower temperatures. In situ introduction of metal oxides while synthesizing the mesoporous material can further enhance its reaction activity.
[0044] 2. In the preparation method provided by the present invention, the template, silicon source, component c) source and solvent are first mixed, and then ammonia water is added dropwise, and the obtained solid is mixed with component b) source and precipitant after aging and roasting, and then subjected to three hydrothermal reactions in sequence, and then treated with a sulfating agent and roasted to obtain the catalyst. The method is simple to operate, economically feasible, and easy to industrially apply. The catalyst prepared by the method has a suitable B acid amount and a strong L acid amount distribution, is suitable for toluene disproportionation and transalkylation reactions, and has the characteristics of low reaction temperature, low hydrogen consumption, and high conversion rate.
[0045] 3. In the prior art, the reaction temperature of toluene disproportionation and transalkylation reaction is generally required to be relatively high, usually at 300-500°C. The solid acid catalyst provided by the present invention is used for toluene disproportionation and transalkylation reaction, and has the characteristics of low reaction temperature, low hydrogen consumption and high conversion rate. Further preferably, the solid acid catalyst provided by the present invention is suitable for toluene disproportionation and transalkylation reaction below 300°C. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below in conjunction with embodiments, but is not limited to the following embodiments.
[0047] In the present invention, the solid nuclear magnetic resonance spectrum using trimethylphosphine as the probe molecule ( 31 The P MAS NMR test method is as follows: after activating the sample under vacuum, a certain amount of trimethylphosphine molecules are adsorbed on the sample to be tested in situ, and the sample is loaded in a glove box protected by N2. The test is performed using a Bruker AVANCEⅢ400WB solid-state nuclear magnetic resonance instrument with a rotor diameter of 4mm and a sample speed of 12kHz. High-power proton decoupling test 31 P MAS NMR spectrum, the test results are calibrated and analyzed using NH4H2PO4 as the standard reference. The B acid content is determined by the sample between 0 and -5 ppm. 31 The P MAS NMR peak area is calculated. The acidity of the strong L acid is determined by the sample concentration between -5 and -35 ppm. 31 P MAS NMR peak areas were calculated.
[0048] In the present invention, % refers to mass percentage unless otherwise specified.
[0049] [Example 1]
[0050] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 71.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After the mixture A1 was aged at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0051] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0052] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0053] [Example 2]
[0054] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 74.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 1% of the total weight of the catalyst. After aging the mixture A1 at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0055] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0056] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0057] [Example 3]
[0058] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 71.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After aging the mixture A1 at 30°C and a relative humidity of 30% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0059] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0060] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0061] [Example 4]
[0062] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 83.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After the mixture A1 was aged at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0063] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 11% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0064] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0065] [Example 5]
[0066] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 71.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After the mixture A1 was aged at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0067] Weigh 10g of A2, mix with tetrabutyl titanate and urea in deionized water and stir thoroughly, wherein the weight percentage of Ti (calculated as TiO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0068] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0069] [Example 6]
[0070] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 71.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After the mixture A1 was aged at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0071] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 135, 155 and 175℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0072] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0073] [Example 7]
[0074] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 74.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 1% of the total weight of the catalyst. After aging the mixture A1 at 30°C and a relative humidity of 30% for 20h, it was calcined at 350°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0075] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 145, 165 and 185℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0076] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0077] [Example 8]
[0078] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.02: 70: 0.1: 20, wherein tetraethyl orthosilicate accounts for 83.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 5% of the total weight of the catalyst. After aging the mixture A1 at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0079] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 10% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, and perform hydrothermal reaction at 125, 155 and 175℃ for 10h respectively, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0080] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0081] [Comparative Example 1]
[0082] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 71.5% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After the mixture A1 was aged at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0083] Weigh 10g of A2, mix with tin chloride and urea in deionized water and stir thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain mixture A2. Transfer mixture A2 into a hydrothermal kettle, hydrothermally react at 170℃ for 48h, wash with deionized water and dry at 90℃ for 12h to obtain solid powder A3. Use 1mol / L dilute sulfuric acid as the sulfation reagent, stir with solid powder A3 at 30℃ for 10h, dry at 90℃ for 10h, and calcine at 600℃ for 5h to obtain catalyst C1.
[0084] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0085] [Comparative Example 2]
[0086] P123, tetraethyl orthosilicate, ethanol, and nickel nitrate were stirred at 35°C. After fully dissolved, diluted ammonia water was added dropwise to the system within 0.2h, and stirred at 35°C for 20h to obtain a mixture A1, wherein the molar ratio of each raw material is tetraethyl orthosilicate: P123: ethanol: NH3: H2O = 1: 0.05: 100: 0.5: 20, wherein tetraethyl orthosilicate accounts for 73% of the total weight of the catalyst in terms of SiO2, and the weight percentage of Ni accounts for 4% of the total weight of the catalyst. After aging the mixture A1 at 50°C and a relative humidity of 50% for 48h, it was calcined at 400°C for 4h to obtain a mesoporous silica material A2 loaded with Ni.
[0087] Weigh 10g of A2, mix it with tin chloride and urea in deionized water and stir it thoroughly, wherein the weight percentage of Sn (calculated as SnO2) is 23% of the total amount of the catalyst, and the molar ratio of Sn to urea is 1:10, to obtain a mixture A2. Transfer the mixture A2 into a hydrothermal kettle, and perform hydrothermal reactions at 145, 165 and 185°C for 10h respectively, wash it with deionized water, and dry it at 90°C for 12h to obtain a solid powder A3, which is calcined at 600°C for 5h to obtain a catalyst C1.
[0088] The evaluation conditions of the catalyst are as follows: 5 g of catalyst C1 is weighed and loaded into a fixed bed reactor, 80 mL / min of hydrogen is introduced, the temperature is maintained at 460°C for 2 hours at a pressure of 4 Ma, the temperature is lowered to 285°C, the hydrogen-to-hydrocarbon molar ratio is adjusted to 0.6, and after the temperature stabilizes, the reaction raw materials toluene and 1,2,4-trimethylbenzene (mass ratio of 1:1) are introduced for reaction for 18 hours. The reaction results are shown in Table 1.
[0089] Table 1 Catalyst evaluation results
[0090]
[0091]
[0092] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A solid acid catalyst, characterized in that Based on the weight of the catalyst, the solid acid catalyst comprises, by mass fraction: a) 50% to 98% of a silicon oxide carrier; b) 1% to 30% of at least one metal selected from Group IVB and Group IVA, calculated as the corresponding metal oxide; c) 0.01% to 10% of at least one metal selected from Group VIB and Group VIII; d) 0.1% to 10% sulfate ion; The ratio of the B acid content to the strong L acid content of the catalyst is 20:1 to 1:
20.
2. The catalyst according to claim 1, characterized in that The ratio of the B acid content to the strong L acid content of the catalyst is 10:1 to 1:10, and more preferably 10:1 to 1:
5.
3. The catalyst according to claim 1, characterized in that The silicon oxide of component a) is mesoporous silicon oxide; and / or, component b) is at least one selected from Zr, Ti, Sn, preferably Sn; And / or, component c) is at least one selected from Cr, Mo, W, Co, Ni, and Ru, more preferably at least one selected from W and Ni.
4. A method for preparing the catalyst according to any one of claims 1 to 3, comprising: (1) mixing a template, a silicon source, a source of component c), and a solvent, and then dropwise adding ammonia water to obtain a mixture; (2) aging the mixture obtained in step (1) to obtain a gel, and then subjecting the mixture to a first calcination to obtain a solid; (3) mixing the solid obtained in step (2), the source of component b) and the precipitant, and performing a first hydrothermal reaction, a second hydrothermal reaction and a third hydrothermal reaction, and then separating to obtain a solid; (4) treating the solid obtained in step (3) with a sulfating agent, and then subjecting the solid to a second calcination to obtain the catalyst; In step (3), the reaction temperature of the second hydrothermal reaction is higher than the reaction temperature of the first hydrothermal reaction; and the temperature of the third hydrothermal reaction is higher than the reaction temperature of the second hydrothermal reaction.
5. The preparation method according to claim 4, characterized in that: In step (3), the reaction temperature of the second hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the first hydrothermal reaction; and the reaction temperature of the third hydrothermal reaction is 10 to 50° C. higher than the reaction temperature of the second hydrothermal reaction.
6. The preparation method according to claim 4, characterized in that: In step (3), the temperature of the first hydrothermal reaction is 120-150° C., and the time is 2-20 h; and / or, the temperature of the second hydrothermal reaction is 150-170° C., and the time is 2-20 h; and / or, the temperature of the third hydrothermal reaction is 170-200° C., and the time is 2-20 h.
7. The preparation method according to claim 4, characterized in that: In step (1), the template is at least one of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123, hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride, preferably P123; And / or, the silicon source is tetraethyl orthosilicate; And / or, the solvent is ethanol; And / or, the source of component c) is a metal salt containing component c), preferably a soluble metal salt; further, the source of component c) is at least one of nitrates, acetates and chlorides containing the metal of component c).
8. The preparation method according to claim 4, characterized in that: In step (1), the molar ratio of the feed materials is, silicon source is calculated as SiO2: template: solvent: NH3: H2O = 1: 0.001 ~ 1: 20 ~ 200: 0.001 ~ 1: 1 ~ 50, preferably, silicon source is calculated as SiO2: template: solvent: NH3: H2O = 1: 0.01 ~ 0.1: 50 ~ 150: 0.01 ~ 0.5: 10 ~ 30.
9. The preparation method according to claim 4, characterized in that: In step (2), the conditions for the first calcination are: a calcination temperature of 200 to 700° C., preferably 300 to 500° C., and a calcination time of 1 to 10 hours, preferably 2 to 5 hours.
10. The preparation method according to claim 4, characterized in that: In step (4), the sulfating agent is at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate; And / or, the temperature of the sulfation treatment is 15 to 40° C. and the time is 2 to 20 hours.
11. The preparation method according to claim 4, characterized in that: In step (4), the atmosphere of the second calcination is an oxygen atmosphere, preferably air; the temperature of the second calcination is 300 to 650° C., and the time is 2 to 20 hours.
12. Use of the catalyst according to any one of claims 1 to 3 or the solid acid catalyst prepared by the preparation method according to any one of claims 4 to 11 in toluene disproportionation and transalkylation reactions.
13. The use according to claim 12, characterized in that: The reaction conditions of the application are: reaction temperature of 100-500°C, preferably 100-300°C, more preferably below 300°C; and / or reaction pressure of 1.0-8.0MPa; and / or hydrogen-to-hydrocarbon molar ratio of 0.1-10, preferably 0.1-5; and / or liquid raw material weight space velocity of 0.5-10h -1 .
Citation Information
Patent Citations
Catalyst of toluene disproportionation and alkyl transference, and preparation method and application thereof
CN102909066A
Catalyst of toluene disproportionation and alkyl transference, and preparation method and application thereof
CN102909068A
Toluene disproportionation and transalkylation two-component catalyst and preparation method thereof
CN113492016A
Solid super acidic catalyst and preparation method thereof
CN101745407A
Preparation method of zirconium-containing solid super acid
CN104971770A